2018
DOI: 10.3389/fmed.2018.00087
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transcriptomics on Our Understanding of Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a lethal fibrotic lung disease characterized by aberrant remodeling of the lung parenchyma with extensive changes to the phenotypes of all lung resident cells. The introduction of transcriptomics, genome scale profiling of thousands of RNA transcripts, caused a significant inversion in IPF research. Instead of generating hypotheses based on animal models of disease, or biological plausibility, with limited validation in humans, investigators were able to generate hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 129 publications
1
39
0
Order By: Relevance
“…The use of informatics-based analysis of gene expression data to identify genes, pathways and mechanisms of relevance in organs and tissues of interest has become an established path to uncovering important pathobiology. [19] scRNAseq methodologies are rapidly advancing and recent studies have provided important insights into the heterogeneity and diversity of mesenchymal, epithelial and alveolar macrophage populations in the setting of pulmonary fibrosis. [2022] However, spatial information, and therefore the precise anatomical location from which the cells are derived, is lost during single cell dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of informatics-based analysis of gene expression data to identify genes, pathways and mechanisms of relevance in organs and tissues of interest has become an established path to uncovering important pathobiology. [19] scRNAseq methodologies are rapidly advancing and recent studies have provided important insights into the heterogeneity and diversity of mesenchymal, epithelial and alveolar macrophage populations in the setting of pulmonary fibrosis. [2022] However, spatial information, and therefore the precise anatomical location from which the cells are derived, is lost during single cell dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…High throughput molecular studies have yielded valuable insights into lung pathobiology, yet many studies are limited by low sample number and lack validation cohorts [17]. Individuals diagnosed with the same disease may have widely disparate clinical courses and responses to therapies, underscoring the need to generate biorepositories with comprehensive cellular and molecular phenotyping that can facilitate personalised approaches to disease classification and management.…”
Section: Implications For Current and Future Applicationsmentioning
confidence: 99%
“…Those features could be just the consequence of stochastic events and disorganisation. However, several transcriptomic analyses showed that IPF could be classified and separated from other interstitial lung fibrotic diseases, suggesting that underlying patterns and laws do drive this disease [11]. In the present article, we will examine whether an aberrant transcriptional integration of those pathways may be involved honeycombing; and 4) hyperplastic alveolar epithelial type 2 cell (AE2C) (lower image is a magnification of the dashed box).…”
Section: Introductionmentioning
confidence: 97%
“…Thus, small changes in the dynamic of developmental signalling networks in chronically injured lungs may have major impacts on the different lung cell populations leading to the generation of diverse and even atypical phenotypes. Indeed, single-cell transcriptomic methods applied to the fibrotic lung identified an alveolar epithelial cell population with mixed differentiation state [11,37].…”
Section: Introductionmentioning
confidence: 99%